(Re)defining their place at the table: Frank discussions by adults with disabilities on contemporary self‐advocacy. Issue 3 (30th January 2022) - Miller, Amanda L.; Frye, David; Green, Thelma; Mitchell, Cheri; Garcia, George; Huereña, Juliana; Moore, Teresa; Turnage, Vicki
Abstract: Adults with disabilities have long been at the forefront of disability advocacy in the United States. Grounded in the tenets of radical disability studies and principles of disability justice, this study explored the lived experiences of 12 adults with disabilities, including intellectual disability and developmental disabilities, with a particular focus on self‐advocacy. Two focus groups were primary data sources. Three participants and one university‐based researcher analyzed the data collaboratively. Iterative data collection and analysis yielded 8 primary codes and 22 subcodes. We discuss a subset of our findings, focusing on three major themes. The findings illuminated how adults with disabilities conceptualised self‐advocacy expansively, including self, other, and the collective. Participants also described problems they faced advocating. Finally, adults with disabilities shared solutions to inequities at individual, group, and societal levels. This project illustrates the importance of centering adults with disabilities in research and policy with implications for future thought.